Toxic environmental exposures and kidney health in children - Weidemann, Darcy K. (Pediatr Nephrol, 2015)
High-level exposures to a number of agents are known to have direct nephrotoxic effects in children. A growing body of literature supports the hypothesis that chronic, relatively low-level exposure to various nephrotoxicants may also increase the risk for chronic kidney disease (CKD) or accelerate its progression. In this review we highlight several environmental nephrotoxicants and their association with CKD in children and adolescents. We also discuss unique epidemiological challenges in the use of kidney biomarkers in environmental nephrotoxicology.